An Analysis of Underwriting Performance of Nepalese Non-Life Insurers (Journal of Insurance Studies in South Asia, 2025)
The study depicts the performance of non-life insurers in terms of their net premium income with reinsurance commission received and the expense made through the net claims, agency & reinsurance commission paid and management expenses. By netting the income versus expenses aroused of core business function, underwriting profit or loss are derived which formed the basis of this study. The underwriting profit is still in the P/L accounts of insurer but with much diminishing pattern. If other variables are kept constant the higher expenses ratio having 6.3% CAGR will surpass the lower income ratio having 4.15% CAGR in coming 11.3 years. Methodology of ANOVA is used in this study to find out the relation between the underwriting profit and net premium income by using simple linear regression. Findings directs that the underwriting profit will be converted into near future if the rate of risk premium does not rise or the net claims are not reduced by this industry.